INSTITUTIONAL ENVIRONMENT AS A FACTOR IN ENSURING ENTERPRISE COMPETITIVENESS (Development Service Industry Management, 2025)
The article comprehensively explores the institutional environment as a fundamental factor determining the competitiveness of enterprises in the modern economy, characterized by transformational changes, globalization, and growing uncertainty. The research emphasizes that the effectiveness of enterprises increasingly depends not only on resource capacity, innovation, or management efficiency, but also on the quality of institutions that define the “rules of the game” in the market. Institutions - both formal (laws, regulations, governance mechanisms) and informal (norms, values, and trust) - create the framework for economic behavior, influence the stability of property rights, and ensure predictability in business activities. According to D. North and O. Williamson, institutional quality shapes transaction costs, market coordination, and the efficiency of economic exchanges, thereby forming the foundation for sustainable competitive advantages.The article systematizes the theoretical approaches of foreign and Ukrainian scholars who underline the role of institutions in shaping economic performance and competitiveness. It is noted that in developed countries, institutional stability, effective regulation, transparent governance, and strong financial markets constitute the backbone of enterprise competitiveness. In this context, institutions act as catalysts for innovation, entrepreneurship, and investment, ensuring the efficient allocation of resources and stimulating fair competition. For transitional economies, including Ukraine, institutional transformation is particularly significant due to the necessity of rebuilding a system of trust, reducing transaction costs, and integrating into global value chains.The structure of the institutional environment of enterprise competitiveness is detailed, encompassing several key subsystems: legal and regulatory institutions that determine the protection of ownership and contractual enforcement; financial and economic institutions that provide access to capital and investment resources; political institutions responsible for ensuring macroeconomic stability and transparency; social and cultural institutions that influence business ethics, human capital, and corporate responsibility; and digital institutions that promote open data, electronic governance, and innovation ecosystems. Their interaction ensures the coherence of state policy, market mechanisms, and social initiatives, forming a holistic institutional architecture conducive to sustainable competitiveness.The paper highlights that for Ukraine, improving institutional quality has become a strategic imperative in the context of post-war economic recovery and European integration. The author substantiates the need for comprehensive reforms aimed at judicial independence, regulatory simplification, development of digital infrastructure, and strengthening of public-private partnerships. Special attention is paid to the implementation of European standards of governance (transparency, accountability, rule of law) and the creation of digital platforms (such as Diia.Business, eData, ProZorro, and FoodDataHub) that enhance information accessibility, reduce administrative barriers, and support business decision-making.It is concluded that an effective institutional environment forms the foundation for strengthening enterprise competitiveness by reducing uncertainty, enhancing innovation potential, and ensuring long-term investment stability. Institutional modernization, based on good governance, digital openness, and economic inclusivity, should become a central component of Ukraine’s sustainable development strategy. Ultimately, institutional quality serves not only as a mechanism for regulating economic processes but also as a driving force for innovation, productivity growth, and integration into the European and global economic space.
Keywords: institutional environment; enterprise competitiveness; institutions; economic performance; state policy; innovation; digital transformation; sustainable development; Ukraine